1999
DOI: 10.1002/oti.101
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment versus power: consumer participation in mental health services

Abstract: Consumer participation is regarded as increasingly important in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Similarly, from Connor's (1999, p. 81) personal consumer perspective, consumers felt that ‘their experience of mental illness and the expertise gained because of this experience while sometimes noted is not usually valued, or even believed’. In Honey's (1999, p. 270) study, mental health consumers acknowledged that having their voices heard and their contributions valued was associated with an increase in confidence and self‐esteem. Honey (1999, p. 270) also noted that ‘consumers have a great deal of knowledge which should not be discounted because it is different in character from the knowledge of health workers’.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, from Connor's (1999, p. 81) personal consumer perspective, consumers felt that ‘their experience of mental illness and the expertise gained because of this experience while sometimes noted is not usually valued, or even believed’. In Honey's (1999, p. 270) study, mental health consumers acknowledged that having their voices heard and their contributions valued was associated with an increase in confidence and self‐esteem. Honey (1999, p. 270) also noted that ‘consumers have a great deal of knowledge which should not be discounted because it is different in character from the knowledge of health workers’.…”
Section: Discussionmentioning
confidence: 98%
“…In Honey's (1999, p. 270) study, mental health consumers acknowledged that having their voices heard and their contributions valued was associated with an increase in confidence and self‐esteem. Honey (1999, p. 270) also noted that ‘consumers have a great deal of knowledge which should not be discounted because it is different in character from the knowledge of health workers’.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Roper & Happell ). Moreover, studies have found that consumer leaders in mental health organizations may be ambivalent about assuming power for fear that their views and concerns may not represent those of consumers at large (Honey ; Happell & Roper ).…”
Section: Introductionmentioning
confidence: 99%
“…Townsend (1998) asked if institutions have the ability and the will to introduce radically different ways of managing, so that hierarchies can be set aside to make client empowerment a reality. Client empowerment, autonomy and participation can only be achieved 'out there', in the community, so it should be a task for society and institutions as well as for individuals (Townsend, 1998;Honey, 1999). One could discuss to what extent occupational therapists can steer an institution's concept of care in the direction of client-centred or client-demanded care.…”
Section: Discussionmentioning
confidence: 97%